The Meaning Of Village Fund Financial Accountability In Lembang Buntu La'bo' (A Phenomenology Study) - Yohanis Lotong Ta’dung; Dwibin Kannapadang (LP2M IAIN Palopo, 2025)
This research aims to detect and understand the meaning of financial accountability of village funds in Lembang Buntu La'bo' Tana Toraja from a phenomenological perspective. This research was conducted in Lembang Buntu La'bo' with Lembang financial management actors as the informants. This research uses an interpretive paradigm with a phenomenological approach. The results of this study indicate that the meaning of financial accountability starts from the planning, implementation, reporting and accountability processes. This research is expected to contribute knowledge in the form of theory development, becoming additional literature on the behavior of Lembang financial management actors towards financial accountability practices. Transparency and accountability are the spirit of accountability accounting.